PERBANYAKAN IN VITRO TANAMAN KENTANG (Solanum tuberosum [L.] cv. Granola) DENGAN PENAMBAHAN META-TOPOLIN PADA MEDIA MODIFIKASI MS (Murashige & Skoog) - Setiawati, Tia; Zahra, Auliya; Budiono, Rully; Nurzaman, Mohamad (Metamorfosa: Journal of Biological Sciences; Vol 5 No 1 (2018), 2018)
The aim of this research was to get the best combination of MS modified media with meta-Topolin (mt) concentration which can increase the growth of potato ( Solanum tuberosum L.) in vitro. This research employed Completely Randomized Design (CRD) with single factor in 12 treatments combination of MS modified media with meta-Topolin concentration. The MS modified media used consisted of ½ MS, ¾ MS and full MS, while meta-Topolin concentrations consisted of  0, 1, 2, and 3 ppm. Each treatment was repeated three times. Data were analyzed using Analysis of Variance (Anova) and Duncan Multiple Range Test at 5% level. The results showed that the combination of ½  MS media + 2 ppm meta-Topolin was the best treatment that resulted in the average plant height of 5.07 cm, the buds number of 7.0, the shoot length of 3.37 cm, the number of leaves of 29.67, root number of 5.67 roots, and root length of 5.91 cm.